ФУНКЦИОНАЛЬНОЕ СОСТОЯНИЕ ЭНДОТЕЛИЯ И ПОЧЕК У БОЛЬНЫХ АРТЕРИАЛЬНОЙ ГИПЕРТЕНЗИЕЙ В СОЧЕТАНИИ С САХАРНЫМ ДИАБЕТОМ 2 ТИПА - М. Е. Стаценко; М. В. Деревянченко; М. Н. Титаренко; О. Р. Пастухова (SINAPS LLC, 2015)
Aim: To study endothelial function and renal function in patients with arterial hypertension (AH) combined with diabetes mellitus (DM) type 2. Materials and methods. The study included 120 patients with arterial hypertension stage II-III in age from 40 to 65 years: 60 diabetic hypertensive patients (study group) and 60 non-diabetic hypertensive patients (control group). We studied endothelial and renal function. Results. We carried out a parallel analysis of the plasma parameters and organs (urine) component of endothelium in relation to the assessment of renal function. We found a statistically significant increase in the concentration of endothelin 1 (ET-1) in serum and decrease of nitric oxide metabolites (NO) in the urine of hypertensive patients with type 2 diabetes compared with those without type 2 diabetes (1,81 ± 0,07 vs 1,54 ± 0,07 pg / ml and 654,7 ± 45,9 vs 792,1 ± 39,4 M, respectively). In assessing renal function had higher values of proteinuria (PU), albuminuria (AU), as well as reduced glomerular filtration rate (GFR) in the intervention group compared with the control (775,2 ± 40,2 vs 476,5 ± 32, 9 mg / g, 323,3 ± 9,7 vs 190,6 ± 13,1 mg / g 59,2 ± 1,2 vs 74,6 ± 1,8 ml / min / 1.73 m2, respectively, p <0.05). There were significant correlation between endothelial and renal function. Conclusion. The study shows that while the comparable values of SBP office and DBP office the severity of endothelial dysfunction was significantly higher among patients with hypertension combined with type 2 diabetes compared to patients with hypertensive patients without type 2 diabetes. The results of evaluation of the urinary and plasma components of endothelial function in parallel with the analysis of renal function lets to assume that the forecast of hypertensive patients with type 2 diabetes determines not only from the initial value of BP, as the state of the target organ (endothelium, kidney).